INTEGRASI PENDEKATAN PSIKOTERAPI DALAM DAKWAH ISLAM MELALUI STUDI KASUS METODE DAKWAH TERAPEUTIK USTADZ ADI HIDAYAT - Mardiana, Puja; Natsar Tasywilurrahman; Wulan Nur Alifah; Ahmad Fauzi Ramdani; Virni Nur Pratami (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
This research examines the concept and implementation of therapeutic da'wah developed by Ustadz Adi Hidayat, an innovative approach that integrates Islamic teachings with the principles of modern psychology. Using a qualitative method with a case study approach, this research investigates how Ustadz Adi Hidayat utilises Qur'anic verses and hadith as a source of soul healing and practical solutions to psychological problems. The results show that this therapeutic da'wah approach has a significant positive impact on the mental and spiritual health of the congregation, including increased serenity, happiness, and quality of interpersonal relationships. Although it faces challenges in terms of improving the competence of preachers in the field of psychology, this method opens up great opportunities for further development, especially through the utilisation of digital technology. In conclusion, Ustadz Adi Hidayat's therapeutic da'wah offers an effective model of integrating religious teachings with contemporary psychological needs, demonstrating the importance of a holistic approach in modern da'wah practice.